2012
DOI: 10.1177/1040638712470946
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence and risk factors associated with Caprine herpesvirus 1 in dairy goat flocks in a semiarid region of northeastern Brazil

Abstract: A cross-sectional study was carried out to determine the flock-level seroprevalence of Caprine herpesvirus 1 (CpHV-1) and Bovine herpesvirus 1 (BoHV-1) and 2 (BoHV-2) and risk factors associated with CpHV-1 in dairy goat flocks from a semiarid region of northeastern Brazil. A total of 1,034 serum samples from 110 flocks were collected from March 2009 through March 2010. A structured questionnaire focusing on variables related to risk factors for CpHV-1 infection was given to each farmer at the time of blood co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…However, 89% (156/174) of the goats tested positive only to CpHV-1 antibodies, indicating that in these animals, there were no cross-reactions with BoHV-1. Similar results were reported in previous studies (19,25). Martin et al (1990) reported that antibodies against CpHV-1 were shown to have no potential to neutralize BoHV-1.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, 89% (156/174) of the goats tested positive only to CpHV-1 antibodies, indicating that in these animals, there were no cross-reactions with BoHV-1. Similar results were reported in previous studies (19,25). Martin et al (1990) reported that antibodies against CpHV-1 were shown to have no potential to neutralize BoHV-1.…”
Section: Discussionsupporting
confidence: 80%
“…However, antibodies against BoHV-1 protected against CpHV-1. Silva et al (2013) reported that all samples were shown to be positive for BoHV-1 showed positivity for CpHV-1 by VNT at the same time. By performing ELISA and VNT for CpHV-1 we have found a positivity of 87.63%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovered animals become latently infected and the virus is detected in the sacral ganglia (Camero et al, 2010;Tempesta et al, 1999b). Spreading of the infection and seroconversion in a flock usually follow virus reactivation in infected animals during the mating season (Koptopoulos et al, 1988;Papanastasopoulou et al, 1990) and the use of natural mating is considered as a risk factor (Silva et al, 2013). Indeed, virus reactivation has been observed and reported only in coincidence with estrus in animals with low specific antibody titers (Tempesta et al, 1998).…”
Section: Caprine Herpesvirus Infection 1 (Cphv-1) Is a Widespread Infmentioning
confidence: 98%
“…leczenia kortykosteroidami, ciąży, transportu, wprowadzeniu zwierzęcia do nowego stada, innych chorób, złych warunków hodowli, a nawet nieodpowiedniej diety (91,97). W ostrej fazie zakażenia wirus jest uwalniany przez drogi oddechowe, wydzielinę z oczu oraz z narządów płciowych (78). Do zakażenia może dojść również na skutek kontaktu ze skażoną żywnością, wodą, naczyniami lub narzędziami (91).…”
Section: Zakażenia Herpeswirusowe Zwierząt Gospodarskich I Towarzysząunclassified